2014
DOI: 10.1158/1541-7786.mcr-14-0124
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mTORC1–Mediated Metabolic Addiction Overcomes Fludarabine Resistance in Malignant B Cells

Abstract: mTORC1 activation occurs frequently in cancers, yet clinical efficacy of rapalogs is limited due to the associated activation of upstream survival pathways. An alternative approach is to inhibit downstream of mTORC1; therefore, acquired resistance to fludarabine (Flu), a purine analog and anti-metabolite chemotherapy, active agent for chronic lymphocytic leukemia (CLL) was investigated. Elevated phospho-p70S6K (T389), an mTORC1 activation marker, predicted Flu resistance in a panel of B-cell lines, isogenic Fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Given that the dependency of ABT-199-R cells on MCL-1 is regulated by the PI3K/mTOR pathway, we next asked whether these cells could be sensitized to ABT-199 by targeting the PI3K or mTOR pathways. We used the PI3K δ and mTORC1 inhibitors, GS-1101 and RAD001, respectively, as before, 32 , 33 in combination with ABT-199. Cell viability analyses with Annexin V-PI indicated that GS-1101 in combination with ABT-199 sensitized SU-DHL-6 ABT199-R cells more than the RAD001+ABT-199 combination ( Figures 6a and d ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that the dependency of ABT-199-R cells on MCL-1 is regulated by the PI3K/mTOR pathway, we next asked whether these cells could be sensitized to ABT-199 by targeting the PI3K or mTOR pathways. We used the PI3K δ and mTORC1 inhibitors, GS-1101 and RAD001, respectively, as before, 32 , 33 in combination with ABT-199. Cell viability analyses with Annexin V-PI indicated that GS-1101 in combination with ABT-199 sensitized SU-DHL-6 ABT199-R cells more than the RAD001+ABT-199 combination ( Figures 6a and d ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both metformin, a respiratory chain complex I inhibitor, and rapamycin similarly synergized with dasatinib in inducing apoptosis in the sensitive subset [104]. Sharma et al focused on the metabolic response to chemotherapeutic agent fludarabine: CLL cells, namely MEC-1 and 2 cell lines and primary samples showed an entirely similar profile to fludarabine resistant cells, a profound mTOR activation that caused an overall increase in glycolysis and OXPHOS rates, combined with an upregulation of purine biosynthesis [105]. An interesting observation was made by Siska et al: chronic and acute B leukemia cells can induce metabolic changes in T lymphocytes by reducing their signaling through mTOR, thus slowing down their GLUT1-mediated glucose import and glycolytic rates, ultimately impairing their anti-leukemic action [106].…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…23 Complete deletion of the TORK kinase (TORK) gene in mouse B cells resulted in impaired germinal center formation. 24 Inhibition of mTORC1 by rapamycin in CLL cells results in increased fludarabine sensitivity 25 and inhibition of cytosine guanine dinucleotide-induced proliferation of CLL cells. 26 ATM, ATR, and DNA-PK are critical regulators of the DNA damage repair (DDR) pathway.…”
Section: Introductionmentioning
confidence: 99%